Worship through Infaq and Sadaqah for Education Programs at the Muhammadiyyah Zakat, Infaq, and Sadaqah Institution in Cirebon - Leliya, Leliy; Farhan, Muhammad; Wasman, Wasman; Annisa, Dila; Hakim, Fadlih Abdul (Strata Law Review, 2024)
LAZISMU (Lembaga Zakat Infaq dan Shadaqah Muhammadiyah / Muhammadiyah Zakat, Infaq, and Sadaqah Institution) is an amil zakat institution in which its fundraising activities are obtained from zakat, infaq and shodaqoh which are allocated to one of the educational financing programs. In accordance with the mission of Lazismu Tuparev Kedawung, Cirebon Regency, this education financing program is one of the priorities to reduce the number of children dropping out of school. Because education is the best way to improve the quality of a nation's human resources. This study aims to answer the questions that become the formulation of the problem. "How is the distribution of infaq and shodaqoh in educational programs in Cirebon Regency from the perspective of law number 23 of 2011". This study uses qualitative research, data collected by means of interviews (interviews), observation, documentation and then analyzed and made conclusions so that it is easily understood by oneself and others. From the results of his research, the management and distribution of infaq and shodaqoh zakat in the education program at LAZISMU Cirebon Regency is in accordance with Law No. 23 of 2011 concerning zakat management.